Analisis nilai-nilai Teologi dan Spiritual dalam Surat Al qodar: Telaah tafsir muqorin dalam perspekti Ibnu Katsir dan Quraish Shihab - Ahda Sabiela; Fikriyatul Ilmi (El-Wasathiya: Jurnal Studi Agama, 2025)
This study aims to conduct a comparative analysis of the interpretations of Surah al-Qadr by Ibn Kathir and M. Quraish Shihab, focusing on their methodological approaches and theological meanings. Ibn Kathir represents the classical exegetical model based on riwāyah (transmitted reports), emphasizing textual authenticity and the authority of the Companions, while Quraish Shihab exemplifies a modern hermeneutic and contextual approach through his work Tafsir al-Mishbah. The research applies a qualitative-descriptive method using library research as the data collection technique and employs content analysis combined with comparative textual analysis (muqāranah) on both primary sources. The findings reveal that Ibn Kathir interprets Lailatul Qadr as a cosmic and transcendental event marking divine decree and the descent of revelation, whereas Quraish Shihab views it as a spiritual and moral moment reflecting human awareness of time, devotion, and peace. These differences illustrate a paradigm shift from a theological-normative orientation toward a humanistic-spiritual. The study highlights the significance of integrating classical and contemporary exegesis to construct a contextual understanding of the Qur’an that remains relevant to modern Islamic spirituality. The study implies that the muqāran method can bridge classical and contemporary interpretations, showing that Qur’anic texts contain layered meanings—literal, contextual, and symbolic. The findings encourage Muslims to internalize Lailatul Qadr not merely as a ritual event but as a moment of moral and spiritual transformation that remains relevant to modern Indonesian Islamic life. The novelty of this study lies in its comparative analysis that integrates Ibn Kathir’s classical riwāyah-based exegesis with Quraish Shihab’s contemporary social cultural interpretation, specifically on Surah al-Qadr. This research fills a gap in previous studies that have not examined both interpretations within a unified theological and spiritual framework.